Answer:
y = -5x + 7
Step-by-step explanation:
Slope-Intercept Form: y = mx + b
Step 1: Define
5x + y = -2
Random point (2, -3)
Step 2: Rewrite
y = -5x - 2
m = -5
Step 3: Write parallel line
y = -5x + b
-3 = -5(2) + b
-3 = -10 + b
7 = b
y = -5x + 7
The answer probably would be this 5ab-5ac=d
Answer:
C
Step-by-step explanation:
Answer:
yes very much so
Step-by-step explanation:
yes I don't know why but I am really and truly
Answer:
a) y = (x+2)/3
b) 5
Step-by-step explanation:
f^-1(x) means "f inverse of x". To find the inverse, we simply:
a ) f(x) = 3x -2
y = 3x - 2 --> because f(x) is the same thing as y
x = 3y - 2 --> to find the inverse, we simply just switch x and y
x + 2 = 3y
y = (x+2)/3
b) f^-1(13)
f^-1(13) = [((13) + 2)/3]
f^-1(13) = (15)/3
f^-1(13) = 5